2014
DOI: 10.1186/1471-2148-14-134
|View full text |Cite
|
Sign up to set email alerts
|

Uropygial gland size and composition varies according to experimentally modified microbiome in Great tits

Abstract: BackgroundParasites exert important selective pressures on host life history traits. In birds, feathers are inhabited by numerous microorganisms, some of them being able to degrade feathers or lead to infections. Preening feathers with secretions of the uropygial gland has been found to act as an antimicrobial defence mechanism, expected to regulate feather microbial communities and thus limit feather abrasion and infections. Here, we used an experimental approach to test whether Great tits (Parus major) modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
101
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(108 citation statements)
references
References 65 publications
(106 reference statements)
2
101
0
3
Order By: Relevance
“…For example, when preen oil was removed from feathers of Bohemian waxwings (Bombycilla garrulus), UV chroma increased, suggesting a direct effect of preen oil on structural colour (Pérez-Rodríguez et al, 2011). Feather plucking may thus have modified uropygial gland function and/or induced an infection, as feather mite and microbiome abundance have been shown to influence uropygial gland size and function (Galván and Sanz, 2006;Jacob et al, 2014), and handicapped males showed higher blood sedimentation rate. However, the effect of the handicap treatment on UV chroma was similar in females and males, though the former showed no parallel effect on blood sedimentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, when preen oil was removed from feathers of Bohemian waxwings (Bombycilla garrulus), UV chroma increased, suggesting a direct effect of preen oil on structural colour (Pérez-Rodríguez et al, 2011). Feather plucking may thus have modified uropygial gland function and/or induced an infection, as feather mite and microbiome abundance have been shown to influence uropygial gland size and function (Galván and Sanz, 2006;Jacob et al, 2014), and handicapped males showed higher blood sedimentation rate. However, the effect of the handicap treatment on UV chroma was similar in females and males, though the former showed no parallel effect on blood sedimentation.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms underlying seasonal variation in coloration are not yet well understood, but some hypotheses have been advanced, such as UV bleaching, and bacterial or mechanical degradation (Delhey et al, 2010). In great tits, the brightness of the yellow coloration has been shown to increase with the size of the uropygial gland (Galván and Sanz, 2006), which produces an oil that birds deposit on their feathers, its size and oil composition varying with microbiome composition (Jacob et al, 2014). Moreover, activation of the immune system may induce changes in antioxidant status.…”
Section: Introductionmentioning
confidence: 99%
“…We randomly assigned the nests to three treatments as presented in Jacob et al (2014). First, to favour the bacterial growth in the nests, we used TSB (tryptic soy broth, 40 mg/ L in sterilized distilled water, Sigma), a liquid general growth medium for heterotrophic microorganisms that is commonly used in microbiology.…”
Section: Experimental Designmentioning
confidence: 99%
“…By spraying different solutions into randomly allocated nests, we either favoured or inhibited bacterial growth in active nests during the breeding season (Jacob et al 2014). These treatments led to modifications of both total and keratinolytic cultivable bacterial densities in the nests and, by contamination through contact between birds and their nests, also modified adult feather bacterial loads (Jacob et al 2014). We first tested the hypothesis that bacterial keratinolytic activity on feathers alters colouration in free-living great tits.…”
mentioning
confidence: 99%
See 1 more Smart Citation